T cell activator-carrying extracellular vesicles induce antigen-specific regulatory T cells. (30th August 2021) - Mo, Li-Hua; Han, Hai-Yang; Jin, Qiao-Ruo; Song, Yan-Nan; Wu, Gao-Hui; Zhang, Youming; Yang, Li-Teng; Liu, Tao; Liu, Zhi-Gang; Feng, Yan; Yang, Ping-Chang
Abstract: The mechanism of antigen-specific regulatory T cell (Treg ) induction is not yet fully understood. Curcumin has an immune regulatory function. This study aims to induce antigen-specific Tregs by employing extracellular vesicles (EVs) that carry two types of T cell activators. Two types of T cell activators, ovalbumin (OVA)/major histocompatibility complex-II (MHC-II) and tetramethylcurcumin (FLLL31) (a curcumin analog) were carried by dendritic cell-derived extracellular vesicles, designated OFexo. A murine model of allergic rhinitis (AR) was developed with OVA as the specific antigen. AR mice were treated with a nasal instillation containing OFexo. We observed that OFexo recognized antigen-specific T cell receptors (TCR) on CD4 + T cells and enhanced Il10 gene transcription in CD4 + T cells. Administration of the OFexo-containing nasal instillation induced antigen-specific type 1 Tregs (Tr1 cells) in the mouse airway tissues. OFexo-induced Tr1 cells showed immune suppressive functions on CD4 + T cell proliferation. Administration of OFexo efficiently alleviated experimental AR in mice. In conclusion, OFexo can induce antigen-specific Tr1 cells that can efficiently alleviate experimental AR. The results suggest that OFexo has the translational potential to be employed for the treatment of AR or other allergic disorders. Graphical Abstract: